2006
DOI: 10.1016/j.clpt.2005.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human antithrombin inhibits thrombin formation and interleukin 6 release in human endotoxemia

Abstract: We hypothesized that infusion of recombinant human antithrombin without concomitant heparin would have dose-dependent anticoagulant properties and potentially decrease endotoxin (lipopolysaccharide [LPS])-induced cytokine production. This was a randomized, double-blind, placebo-controlled study in parallel groups enrolling 30 healthy male volunteers. The active treatment groups received infusions of recombinant human antithrombin to increase antithrombin levels to 200% and 500% before infusion of 2 ng/kg endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 61 publications
(132 reference statements)
4
33
0
Order By: Relevance
“…Pharmacodynamic parameters were analyzed with the following commercially-available enzymeimmunoassays: Plasma levels of prothrombin fragment (Enzygnost; F 1 + 2 micro; Dade Behring, Marburg, Germany) as marker of in vivo thrombin generation (14). Plasma levels of soluble E-selectin (sE-selectin) and P-selectin (sP-selectin) (enzyme immunoassay R&D Systems, Oxon, UK) were measured at baseline, 8 hand 24· h as previously described (15).…”
Section: Pharmacodynamic Analysesmentioning
confidence: 99%
“…Pharmacodynamic parameters were analyzed with the following commercially-available enzymeimmunoassays: Plasma levels of prothrombin fragment (Enzygnost; F 1 + 2 micro; Dade Behring, Marburg, Germany) as marker of in vivo thrombin generation (14). Plasma levels of soluble E-selectin (sE-selectin) and P-selectin (sP-selectin) (enzyme immunoassay R&D Systems, Oxon, UK) were measured at baseline, 8 hand 24· h as previously described (15).…”
Section: Pharmacodynamic Analysesmentioning
confidence: 99%
“…Antithrombin III (AT) has anti-coagulatory as well as anti-inflammatory effects [25,26]. According to subgroup analyses of the Kybersept study data [27,28], prognosis in septic patients with disseminated intravascular coagulation (DIC) might be improved with AT administration.…”
Section: Background Of Atmentioning
confidence: 99%
“…Recent studies have shown that ANTⅢ may have powerful anti-inflammatory effects. ANTⅢ has inhibitory effects on endotoxin-induced neutrophil activation and it down-regulates the expression of certain proinflammatory cytokines (TNF-α, IL-6) [23] . It has been used in some of European ICU patients to teat sepsis, but in the USA, it is only FDA approved to treat certain coagulation abnormalities.…”
Section: Live Liver Donors: Are They At a Higher Risk For Post-operatmentioning
confidence: 99%